Adsorption of methylene blue from aqueous solution onto viscose-based activated carbon fiber felts: Kinetics and equilibrium studies - Qi-Xia Liu; Yi-Ru Zhou; Mei Wang; Qian Zhang; Tao Ji; Tian-Ye Chen; De-Cheng Yu (Adsorption Science & Technology)
Two viscose-based activated carbon fiber felts (VACFF-1300 and VACFF-1600) with different specific surface areas and pore structures were prepared via two-step carbonization and steam activation and characterized by SEM observation, N 2 adsorption/desorption isotherms, Fourier-transform infrared, X-ray diffraction and X-ray photoelectron spectroscopy analysis. They were used as adsorbents for the removal of methylene blue dye from aqueous solution, and the adsorption equilibrium and kinetics were studied via batch adsorption experiments and the adsorption mechanisms were investigated. Results showed that the equilibrium data for methylene blue adsorption onto VACFF-1300 and VACFF-1600 fitted well to the Langmuir isotherm model, with maximum monolayer adsorption capacity of 256.1 mg/g and 325.8 mg/g, respectively. Besides, the adsorption kinetics study showed that the adsorption of methylene blue onto the two VACFF samples could be best described by the pseudo second-order model. Moreover, the intraparticle diffusion modelling showed that intraparticle diffusion is rate-controlling for both VACFF-1300 and VACFF-1600, and external diffusion is also a rate-controlling step for the latter.